Response of Increasing NaCl Concentrations on Growth and Proline Content of Tacca leontopetaloides cultured in vitro - Martin, Andri Fadillah; Hapsari, Betalini Widhi; Ermayanti, Tri Muji (ANNALES BOGORIENSES, 2015)
Tacca leontopetaloides (L.) Kuntze which belongs to family Taccaceae is one of tuberous plant useful as an alternative food. This plant contains starch (amylose and amylopectin) similar to that of potato. In addition, this plant also contains secondary metabolites potential for diarrhea, dysentery, and anticancer. In Indonesia, this plant grows at coastal areas i.e. in Sukabumi, Yogyakarta, Garut and Karimunjawa, so this plant was suspected to have high tolerance on salinity stress. The purpose of this research was to investigate the effect of increase in NaCl concentrations on growth and its proline content of T. leontopetaloides grown in vitro. In vitro shoot tips were cultured on MS medium (Murashige & Skoog, 1962) supplemented with NaCl at concentrations of 10; 25; 50; 75; 100; 150 and 200 mM, respectively. After six weeks in culture, shoots height, shoots number, leaves number, fresh weight, as well as their proline content were recorded. The results showed that fresh weight of shoots grown on MS medium supplemented with NaCl from 10 to 100 mM was hogher compared to those of the control treatment. Fresh weight decreased when shoots were cultured on MS medium supplemented with NaCl at more than 100 mM. Height of shoots, number of shoots, and number of leaves decreased along with the increase of NaCl concentrations. The best medium for growth was MS medium supplemented with 25 mM NaCl. In this medium proline content was 15.7 umol/g FW. Proline concentrations increased along with the increase of NaCl concentrations. LD50 value was 146 mM NaCl. In conclusion that on MS medium without addition of plant growth regulators, T. leontopetaloides shoot culture was sensitve to the increase of NaCl concentration.